Policy Roundtable on Agri-Food Transformation and Doubling Farmers’ Income in Odisha - International Food Policy Research Institute (CGIAR System Organization, 2022)
Raising farmers’ incomes has been at the forefront of the national policy agenda since the last few years. The doubling farmers’ incomes (DFI) initiative of the Government of Odisha is an ambitious step towards this goal. A majority of farmers in Odisha, like in other parts of India, are smallholders and have low crop yields—lower than national averages in many instances. The challenges faced by these farmers have been exacerbated in the last few decades due to climate change which has resulted in an increased intensity as well as frequency of adverse weather events. There have been several steps taken by the Government of Odisha in the past to overcome these challenges and sustainably enhance the livelihoods of farmers. The outcomes from these steps indicated that there is a need to enhance the coordination of the efforts from various government departments, partners, and other stakeholders for further improvement in outcomes for the farmers.